Land – Sea Interactions’ Analysis: Results-Based Survey Questionnaire Design for Romanian Coastal and Maritime Stakeholder’s Community: Array - Vlasceanu, Elena; Alexandrov, Laura; Mateescu, Razvan; Rusu, Eugen; Niculescu, Dragos (Acta Universitatis Danubius. Œconomica, 2021)
The evaluation of professional-participants’ acting in socio-technical domain related to Marine Spatial Planning (MSP) and the exploration of LSI (Land-Sea Interactions) as main complex approach in MSP need to be addressed in the context of Romanian multi-actor network of the involved maritime and coastal stakeholders. Questionnaire-based research can approach LSI in an integrated manner, combining the expert opinion on many aspects about the complexity of land and sea processes in various specific and measurable interactions. The present analysis of the expert opinion questionnaires, combined within an analysis of LSI processes and outcomes, its shows that the comparative assessment in real and perceived environments can proved an effective and promising advance on semi-quantitative methods of professional MSP planners. Despite surveys’ questionnaires are qualitative methods to assemble information regarding knowledge, facts, and expert opinions from a stakeholder community, it can provide also a semi-quantitative data and information, which can be used for further research, on different relevant MSP features and aspects related LSI within Romanian coastal and marine areas.